2013
DOI: 10.1093/infdis/jit265
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Immunophenotyping Distinguishes Active From Latent Tuberculosis

Abstract: Background. Changes in the phenotype and function of Mycobacterium tuberculosis (M. tuberculosis)-specific CD4+ and CD8+ T-cell subsets in response to stage of infection may allow discrimination between active tuberculosis and latent tuberculosis infection.Methods. A prospective comparison of M. tuberculosis-specific cellular immunity in subjects with active tuberculosis and latent tuberculosis infection, with and without human immunodeficiency virus (HIV) coinfection. Polychromatic flow cytometry was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
105
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(120 citation statements)
references
References 34 publications
11
105
2
2
Order By: Relevance
“…Interestingly, this profile was mycobacterialantigens-specific as stimulation with PHA (mitogen) showed no differences between the groups. A higher proportion of single-TNF-α producing CD4 + and CD8 + T cells in active TB patients compared with latent TB infected (LTBI) or treated patients is well documented, with high single-TNF-α production associated with active TB disease [18][19][20][21][22][23][24][25]. TNF-α controls MTBC infection progression to disease as evidenced by the increase incidence of active TB in patients treated with anti-TNF-α [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this profile was mycobacterialantigens-specific as stimulation with PHA (mitogen) showed no differences between the groups. A higher proportion of single-TNF-α producing CD4 + and CD8 + T cells in active TB patients compared with latent TB infected (LTBI) or treated patients is well documented, with high single-TNF-α production associated with active TB disease [18][19][20][21][22][23][24][25]. TNF-α controls MTBC infection progression to disease as evidenced by the increase incidence of active TB in patients treated with anti-TNF-α [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Phenotyping of immune cells using this approach has shown that different T-cell subsets can differentiate between latent and active TB. Mtb-specific CD4 þ and CD8 þ T-cell subsets secreting TNF-a only, IFN-g only, and dual TNFa/IFN-g appear in higher frequencies in TB patients compared with latently infected individuals (Pollock et al 2013). CD4 þ T cells from individuals latently infected are polyfunctional and express TNF-a, IFN-g, and IL-2 compared with the dominant TNF-a-only response of TB patients (Harari et al 2011).…”
Section: Immune Cell Phenotypingmentioning
confidence: 99%
“…CD4 þ T cells from individuals latently infected are polyfunctional and express TNF-a, IFN-g, and IL-2 compared with the dominant TNF-a-only response of TB patients (Harari et al 2011). During active disease, Mtb-specific CD4 þ T cells also switch from central to effector memory T cells, which are accompanied by a decrease in IL-7 receptor a expression (Pollock et al 2013). PPD-specific TNF-a-only secreting CD4 þ T cells with an effector memory phenotype might therefore discriminate active disease and latent TB infection (LTBI) with promising accuracy.…”
Section: Immune Cell Phenotypingmentioning
confidence: 99%
“…Es importante puntualizar que la respuesta inmune contra la tuberculosis es un proceso muy complejo (1,8,26) . Como se mencionó al inicio, después de la exposición inicial a M. bovis, se desarrolla una respuesta inmune celular T, pero para controlar la proliferación bacteriana se requiere un equilibro muy fino entre la producción de citocinas pro y antiinflamatorias.…”
Section: Cuadro 1 Bovinos Identificados En La Prueba De Ifn-γ Usandounclassified
“…Así mismo, se sabe que diferentes tipos de subpoblaciones de linfocitos T participan en la respuesta inmune contra las micobacterias. Diversos estudios han demostrado que personas con una infección latente de tuberculosis muestran mayores frecuencias de linfocitos T CD4 + trifuncionales, capaces de producir IFN-γ, TNF-α e IL-2, con una mayor capacidad efectora y proliferativa (30) , en contraste con personas con la enfermedad activa que muestran frecuencias elevadas de linfocitos T CD4 + con función simple o doble (26) . Por lo tanto, es posible que la polifuncionalidad pueda correlacionarse con la resistencia a la tuberculosis en humanos y bovinos (31) .…”
Section: Cuadro 1 Bovinos Identificados En La Prueba De Ifn-γ Usandounclassified